Sort by

- Relevance
- |Time

If both

**u**and v are in quadrant II, sin**u**= 5/13, and cosv=-3/5, find cos(**u**+v). cos(**u**+ v) = cos(**u**) cos(v) - sin(**u**) sin(v) sin(**u**) = 5/13 cos(v) = -3/5 we need to find cos(**u**) and...6 Answers · Science & Mathematics · 30/05/2012

**U**, V are vectors. Let**U**=15i, then V=11[cos(51*)i+sin(51*)j]**U**+V=[15+11cos(51*)]i+11sin(51*)j =>**U**+V=21.92i+8.55j |**U**...1 Answers · Science & Mathematics · 04/04/2016

(4

**u**^2+28u+24)/(**u**^2+6u+5) = {4[(**u**^2+7u+6)]}/[(**u**+1)(**u**+5)] = [4(**u**+1)(**u**+6)]/[(**u**+1)/(**u**+5)] Cancel out the factor (**u**+1), then we get = 4(**u**+6)/(**u**+5) = (4u+24)/(**u**+5) Appendix: ...3 Answers · Science & Mathematics · 07/01/2009

**u**and v are both function of x,**u**=f(x) and v=g(x), Dx = d/dx y =**u**^v, what we have to differentiate...differentiation) Dx[ln(y)] = Dx[v] * ln(**u**) + v * Dx[ln(**u**)], chain rule Dx[y] / y = Dx[v] * ln[**u**] + v * Dx...3 Answers · Science & Mathematics · 24/10/2009

well,

**u**can dance. walking is good as long as its high endurance walking.**u**cant be lazy about it either.**u**have to want it bad enough for it to work.2 Answers · Health · 27/08/2007

... don't like it 2 much since itz bad for business thingz and it lookz gross when

**u**take it out but do what**u**want maybe it lookz good on**u**3 Answers · Beauty & Style · 19/05/2010

Write P_n =

**U**_1 ***U**_2 ***U**_3 ...**U**_{n-1} /**U**_n a) Consider...between -1 and 1, so the limit does not exist. b) consider the case a = -2,**U**_1 = 0,**U**_2 = 0 - 0 + 1 = 1**U**_3 = 1 - 2 + 1 = 0 So for...2 Answers · Science & Mathematics · 04/09/2008

**u**(t).v(t) = <-sqrt(t) sint, t, t^(2/3)>.<-sqrt(t) sint, cos^2 t, -t^(1/3)>.**u**(t).v(t) = t*sin^2(t) + t*cos^2(t) - t = t - t = 0 (d/dt)[**u**(t).v(t)] = 0**u**(t...1 Answers · Science & Mathematics · 19/07/2009

**u**^2 + 8u + 7 = 0 (**u**+ 7)(**u**+ 1) = 0 Then**u**has to equal what's in the parentheses set equal to zero:**u**+ 7 = 0 and**u**+ 1 = 0**u**= -7 and**u**= -13 Answers · Science & Mathematics · 06/04/2011

[(

**u**+ h)²/(**u**+ h + 2) - u²/(**u**+ 2)]/h = [(u² + 2uh + h²)/(**u**+ h + 2) - u²/(**u**+ 2)]/h ...1 Answers · Science & Mathematics · 01/06/2013